Dynamics of Democracy in Timor-Leste : The Birth of a Democratic Nation, 1999-2012 - Feijo, R. (Book collections on Project MUSE., 2016)
The Indonesian province of Timor-Leste made international news when it decided to break away from Indonesia in 1999. The decision sparked deadly rampages by pro-integrationist militias, violence that only abated when the UN sent a force to maintain peace and help ease the way to actual independence. This book details the political history of Timor-Leste, both preceding and following the declaration of independence, and it uses the events, consequences, and lessons of that period to help us understand what to expect for similar experiments in democracy building elsewhere in the world.